2002
DOI: 10.1124/jpet.102.034686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antidepressants in Rats Trained to Discriminate Centrally Administered Isoproterenol

Abstract: Previous work has shown that the discriminative stimulus effects of centrally administered isoproterenol are mediated primarily via ␤1-adrenergic receptors. In the present study, this model was used to investigate the ability of antidepressant drugs displaying various pharmacological profiles to stimulate ␤1-adrenergic receptors in vivo; this was assessed by determining whether they substituted for the discriminative stimulus effects of isoproterenol. Rats were trained to discriminate centrally administered is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Consistent with this, it has been shown that antidepressant drugs do not substitute for the discriminative stimulus effects of clenbuterol (Makhay and O'Donnell 1999), which suggests that administration of these drugs does not result in increased stimulation of central b 2 -adrenergic receptors. By contrast, antidepressants with noradrenergic activity, such as desipramine, substitute for the discriminative stimulus effects of centrally administered isoproterenol (Crissman and O'Donnell 2002). Since this effect is mediated by b 1 -adrenergic receptors (Crissman et al 2001), it appears that administration of such antidepressants results in increased stimulation of b 1 -adrenergic receptors in vivo.…”
Section: Introductionmentioning
confidence: 93%
“…Consistent with this, it has been shown that antidepressant drugs do not substitute for the discriminative stimulus effects of clenbuterol (Makhay and O'Donnell 1999), which suggests that administration of these drugs does not result in increased stimulation of central b 2 -adrenergic receptors. By contrast, antidepressants with noradrenergic activity, such as desipramine, substitute for the discriminative stimulus effects of centrally administered isoproterenol (Crissman and O'Donnell 2002). Since this effect is mediated by b 1 -adrenergic receptors (Crissman et al 2001), it appears that administration of such antidepressants results in increased stimulation of b 1 -adrenergic receptors in vivo.…”
Section: Introductionmentioning
confidence: 93%
“…The discriminative stimulus effect of isoproterenol, which is primarily mediated by beta-1 adrenergic receptors (Crissman et al 2001), generalizes to a number of antidepressant drugs (Crissman and O'Donnell 2002), indicating that noradrenergic antidepressants like desipramine indirectly stimulate central beta-1 adrenergic receptors in vivo at behaviorally relevant doses. In rats trained to discriminate the type 4 phosphodiesterase (PDE4) inhibitor rolipram from its vehicle, clenbuterol completely and dobutamine partially substitute .…”
Section: Introductionmentioning
confidence: 99%
“…Activation of either β-1 or β-2 adrenergic receptors produces antidepressant-like effects on DRL behavior (O’Donnell et al , 1994; Zhang et al , 2001, 2005; Zhang et al , 2003). In addition, desipramine and other NE reuptake inhibitors substitute for the β-adrenergic agonist isoproterenol in a drug discrimination task, indicating that β-adrenergic receptors play a role in mediating the effects of desipramine, as well as other NE reuptake inhibitors (Crissman et al , 2001; Crissman and O’Donnell, 2002). Further, repeated treatment with desipramine downregulates β-1, but not β-2, adrenergic receptors in the brain (Paetsch and Greenshaw, 1993).…”
Section: Introductionmentioning
confidence: 99%